Amorphous Metal‐Sulphide Microfibers Enable Photonic Synapses for Brain‐Like Computing. Issue 5 (15th January 2015) - Gholipour, Behrad; Bastock, Paul; Craig, Chris; Khan, Khouler; Hewak, Dan; Soci, Cesare
<x xml:space="preserve">Abstract</x> In the pursuit of all‐optical brain‐like computing, optical axons and photonic synapses are demonstrated using metal‐sulphide microfibers, which allow the generation and propagation of optical action potentials. This gives rise to an all‐optical implementation of a number of interneuronal and intraneuronal communication protocols that underlie learning and cognition in the brain.